Give me your wired and your highly skilled: Measuring the impact of immigration policy on employers and shareholders - Carl Lin (Institute for the Study of Labor (IZA), 2011)
The paper links finance theory to labor economics and political economy in the context of migration and immigration policy. Most research treating the impact of immigration has focused on the consequences for employees as measured by wages, earnings, and employment. Less is known about the impact on employers. We lack answers to basic questions concerning the quantitative impact of immigrants on employer profit, and which employers are most likely to gain (suffer) increased (reduced) profits as a result of immigration. Using event study analysis, I measure the impact of immigration policy on the profit of employers and shareholders, particularly in those industries with high needs for skilled immigrants. The American Competitiveness and Workforce Improvement Act (ACWIA) of 1998 nearly doubled the available number of H-1B visas for skilled foreign workers in FY 1999. It was the first time that the U.S. government raised the annual cap of H-1B visa since 1990. I focus on this bill and analyze whether and by how much its passage increased shareholders' profit. The empirical results show that employers and shareholders in the top H-1B visa user industries enjoyed significant and positive returns with the passage of the ACWIA of 1998. Shareholders in high-tech industries (the top users of H-1B visa, 80% of total) such as Computers and related equipment, and Computer and data processing services gained, respectively, an average 21.54% (15.88 if weighted) and 22.77% (18.11 if weighted) in cumulative excess returns in the month after the Act was passed, while industries with little need for H-1B visas experienced no significant changes in cumulative excess returns. Robustness testing including international factor comparisons, semiparametric modeling and a sample-split Chow structural break test support the results.
urn:nbn:de:101:1-201106202071
Keywords: J61; K31; G12; 330; skilled immigrants; immigration policy; employers; shareholders; event study; H-1B visa